Praktek Pengolahan Sekam Padi Menjadi Pupuk Organik KKN Posko 1 di Desa Padang Mekar Kecamatan Padangguni Kabupaten Konawe - Leni Saleh; Novita Ramadani; M. Rias; Desi Rianti; Tiwal Tiwal; Imel Setiana tagu (Institut Teknologi dan Bisnis Semarang, 2024)
The purpose of this PKM is to carry out the practice of processing rice husks into organic fertilizer in Padang Mekar Village, Padangguni District. The PKM activity was carried out at the house of the Head of Padang Mekar Village on Thursday, October 10, 2024. The community service program (PKM) in Padang Mekar Village in processing rice husks into organic fertilizer has been realized and carried out smoothly through various activities ranging from preparation, counseling, practice and mentoring. With this activity, it shows a positive impact on local PKM participants, namely an increase in knowledge and skills related to processing rice husks into organic fertilizer which has many benefits for farming businesses, especially for rice farmers who are carried out and of course have economic value. This is proven by the activities of filling out the pre-test and post-test questionnaires on participants.